A análise dos objetivos e a relação cintura quadril em praticantes de hidroginástica - Oliveira, Caroline Fernanda Tavares de [UNESP]; Okano, Wagner [UNESP]; Barbosa, Amanda Dias [UNESP]; Neri, Gabrielle [UNESP]; Prado Junior, Milton Vieira do [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The extension project “Swimming in UNESP " aims to extend the practice of aquatic activities to achieve different objectives, such as combating sedentary lifestyle, better physical conditioning , learning and benefit health , among others. In the case of water aerobics classes, the search for health, postural control and fight against physical inactivity are common goals for different age groups. The objective of this study was to investigate among the participants of aerobics who chose to practice in order to health and compare this goal and lifestyle with the numbering waist hip ratio that evaluates the risk to health.

O projeto de extensão “Natação na UNESP” visa estender a prática de atividades aquáticas visando atingir diferentes objetivos, tais como: o combate ao sedentarismo, melhora do condicionamento físico, aprendizagem e benefícios á saúde, entre outros. No caso das aulas de hidroginástica, a busca por saúde, controle postural e combate ao sedentarismo são objetivos comuns para diferentes faixas etárias. Assim, o objetivo deste estudo foi verificar entre os participantes de hidroginástica que escolheram a pratica visando á saúde e comparar este objetivo e estilo de vida com a numeração da relação cintura quadril que avalia o risco á saúde.
Keywords: Water aerobics classes; Body mass index; Waist hip ratio; Hidroginástica; Índice de massa corporal; Relação cintura quadril